2019
DOI: 10.2139/ssrn.3381827
|View full text |Cite
|
Sign up to set email alerts
|

Conservative News Media and Criminal Justice: Evidence from Exposure to Fox News Channel

Abstract: Exposure to conservative news causes judges to impose harsher criminal sentences. Our evidence comes from an instrumental variables analysis, where randomness in television channel positioning across localities induces exogenous variation in exposure to Fox News Channel. These treatment data on news viewership are taken to outcomes data on almost 7 million criminal sentencing decisions in the United States for the years 2005-2017. Higher Fox News viewership increases incarceration length, and the effect is str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Contemporaneous papers by Simonov et al (2020) and Ash et al (2020) use the same idea of identifying variation that we exploit (the Fox News channel position) and the SafeGraph data for social-distancing measures (we use UNACAST and Facebook data instead). There are several notable differences between our approach and that of Simonov et al (2020) and Ash et al (2020). First, we use the earliest available data on the Fox News Channel position (from 2005), while Simonov et al (2020) use the data from 2015, and Ash et al (2020) use channel positions from 2016.…”
Section: Review Of Covid-19-related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Contemporaneous papers by Simonov et al (2020) and Ash et al (2020) use the same idea of identifying variation that we exploit (the Fox News channel position) and the SafeGraph data for social-distancing measures (we use UNACAST and Facebook data instead). There are several notable differences between our approach and that of Simonov et al (2020) and Ash et al (2020). First, we use the earliest available data on the Fox News Channel position (from 2005), while Simonov et al (2020) use the data from 2015, and Ash et al (2020) use channel positions from 2016.…”
Section: Review Of Covid-19-related Literaturementioning
confidence: 99%
“…Media play many important roles in people's lives by transmitting information and shaping beliefs. 1 Such beliefs include trust in government, trust in science, and threat 1 Scholars have shown that slanted media have an impact on voting and political preferences (DellaVigna and Kaplan 2007;Enikolopov et al 2011;Adena et al 2015), collective actions (Zernike 2010), political polarization (Prior 2007;Martin and Yurukoglu 2017), investment decisions (Friebel and Heinz 2014), judicial decisions (Ash and Poyker 2019), city budgets (Galletta and Ash 2019), and candidate entry (Arceneaux et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More broadly, our work contributes to research on the persuasive effects of the news media on on political opinion (Gerber et al, 2009) and various behaviors including political participation (Gentzkow, 2006;Cagé, 2019), voting (Chiang and Knight, 2011;Snyder Jr and Strömberg, 2010;Enikolopov et al, 2011), criminal sentencing decisions (Lim et al, 2015), hurricane evacuations (Long et al, 2019), global warming (Hmielowski et al, 2014), and genocide (Yanagizawa-Drott, 2014). 7 A subset of this work has found a persuasive effect of Fox News on voting behavior (DellaVigna and Kaplan, 2007;Martin and Yurukoglu, 2017) and criminal sentencing (Ash and Poyker, 2019). A related literature has looked at the supply of fake news (e.g., Allcott et al, 2019) and the persuasive effect of fake news on beliefs (Allcott and Gentzkow, 2017;Guess et al, 2018); although persuasive effects have mainly been measured for small news outlets and online social media platforms.…”
Section: Introductionmentioning
confidence: 96%
“…More broadly, our work contributes to research on the persuasive effects of the news media on on political opinion (Gerber et al, 2009) and various behaviors including political participation (Gentzkow, 2006;Cagé, 2019), voting (Chiang and Knight, 2011;Snyder Jr and Strömberg, 2010;Enikolopov et al, 2011), criminal sentencing decisions (Lim et al, 2015), hurricane evacuations (Long et al, 2019), global warming (Hmielowski et al, 2014), and genocide (Yanagizawa-Drott, 2014). 7 A subset of this work has found a persuasive effect of Fox News on voting behavior (DellaVigna and Kaplan, 2007;Martin and Yurukoglu, 2017) and criminal sentencing (Ash and Poyker, 2019). A related literature has looked at the supply of fake news (e.g., Allcott et al, 2019) and the persuasive effect of fake news on beliefs (Allcott and Gentzkow, 2017;Guess et al, 2018); although persuasive effects have mainly been measured for small news outlets and online social media platforms.…”
Section: Introductionmentioning
confidence: 96%